2018
DOI: 10.1002/ar.23787
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Microscopy of Chemically Fixed Human Embryos Performed in University of Tsukuba Since 1999 to 2015

Abstract: Magnetic resonance (MR) microscopy of chemically fixed human embryos performed in University of Tsukuba since 1999 to 2015 was reviewed. More than 1,000 chemically fixed human embryos stored in the Congenital Anomaly Research Center of Kyoto University were used throughout the MR microscopy project, which was divided into three terms. In the first term (1999-2005), 3D MR images of 1,204 embryo specimens were acquired with 128 × 128 × 256 voxels by a super-parallel MR microscope using a 2.35 T horizontal-bore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…17,18 T1-weighted imaging has also been reported to have the advantage of suppressing the signal from the preservation fluid, allowing clear distinction of structures between adjacent tissues in human embryos. The previous study 16 also discussed the appropriate sequence type for embryo K. Kunieda et al…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 T1-weighted imaging has also been reported to have the advantage of suppressing the signal from the preservation fluid, allowing clear distinction of structures between adjacent tissues in human embryos. The previous study 16 also discussed the appropriate sequence type for embryo K. Kunieda et al…”
Section: Introductionmentioning
confidence: 99%
“…Despite these difficulties, many studies have been performed on MR microscopy of human embryos. [14][15][16] The previous study performed MR microscopy of specimens from CS16 to CS22 in 2015. 15 The largest sample used was CS22 with a voxel size of (60 µm) 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it would require a large number of samples to study a whole range of pathologies due to the technique's destructiveness. To overcome this issue, Magnetic Resonance (MR) microscopy has been used for embryo imaging [6] allowing for 3D reconstruction. Nevertheless, this technique has limited contrast for hard tissues and has a limited resolution to evaluate the structures at the tissue scale.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that conventional 1.5T and 3T magnetic resonance imaging (MRI) magnets currently used in clinical setting have shown lower accuracy in examining fetuses below 16 weeks of gestation [ 8 , 9 ], we considered the use of a high-power field magnet of 7T. Significant advances in the development of high-field MRI allowed for important progress in post-mortem fetal imaging [ 10 , 11 ] and numerous published studies have shown good diagnostic accuracy specially for fetal heart examination, describing pm-MRI as an alternative to conventional autopsy [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%